(untitled) (Scientific journal of the Fergana State University, 2025)
This paper explores the efficiency of using a circuit training system to enhance the physical qualities of students in higher education institutions. The findings of the study indicated a positive influence on improving physical fitness, endurance, strength, agility, and speed among students. The incorporation of an individualized approach in training sessions supported the students’ physical advancement. The results were verified through mathematical and statistical analysis, and practical recommendations for refining the educational process were proposed.